2018
DOI: 10.18775/ijmsba.1849-5664-5419.2014.46.1005
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Taxable Capacity in Nigeria

Abstract: This study is centered on the determinants of taxable capacity in Nigeria, with taxable capacity viewed as the ability of the taxed person to bear the burden of the tax in relation to their source of income without experiencing a reduction in standard of living, or margin of profit and investment in the case of firms. The study employed desk survey research design, and data obtained from secondary sources and analysis conducted using the ordinary least square technique. The results from the regression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In a similar study, Ikhatua and Ibadin (2019) showed that tax revenue is determined by agricultural sector productivity, manufacturing sector productivity, capital flight and trade openness using the autoregressive distributed lag model. Moreover, the study of Bassey and Efiong (2018) revealed that the inflation rate has a negative effect on tax revenue generation, while the degree of economic openness and the level of economic development are positively related with tax revenue in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a similar study, Ikhatua and Ibadin (2019) showed that tax revenue is determined by agricultural sector productivity, manufacturing sector productivity, capital flight and trade openness using the autoregressive distributed lag model. Moreover, the study of Bassey and Efiong (2018) revealed that the inflation rate has a negative effect on tax revenue generation, while the degree of economic openness and the level of economic development are positively related with tax revenue in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 99%